SAT0556 EVALUATING RESEARCH PARTICIPANT EXPERIENCE IN A RHEUMATOID ARTHRITIS OBSERVATIONAL STUDY. (June 2019) - Monaghan, Siena; Anderson, James; Planner, Claire; Sanders, Caroline; Verstappen, Suzanne; Sergeant, Jamie
Abstract : Background: Patient and public involvement (PPI) in research is increasingly common (1), but the experience of research participants is rarely evaluated, missing opportunities to gain insights for improving future studies. (2) Observational studies are often used to study natural progression and treatment response in chronic diseases like rheumatoid arthritis (RA). Objectives: We aimed to pilot a participant experience questionnaire in an observational study of RA patients, to gain feedback on the study and evaluate the questionnaire as a feedback tool. Methods: The Rheumatoid Arthritis Medication Study (RAMS) is a large UK prospective observational study of patients with RA or undifferentiated polyarthritis starting methotrexate (MTX) for the first time. Participants were recruited prior to initiation of MTX and followed-up at 3, 6 and 12 months. At visits, disease activity is measured and participants complete a study questionnaire including patient reported outcomes. Participants also complete a weekly diary about their MTX use. (3) A subset of RAMS participants were given a feedback questionnaire at their final visit. The questionnaire was designed by researchers and study coordinators with feedback from patients. Questions addressed the value of participation, study conduct and priorities for future research. Multiple-choice question responses were summarised and key themes were identified in the free-text responses. Results: 201 of 357 (56%) patients eligible to receive the questionnaire completed it. Multiple-choice questions had 100% completion and responses are presented in Table 1 . 189 (94%) participants agreed that participating in RAMS was worthwhile and 180 (90%) would recommend participation to eligible friends and family. The most frequent theme in recommending the study was the desire to "help people" (47%) and most respondents (57%) did not know what future research they would like carried out or did not answer. Conclusion: The majority of RAMS participants were happy to share their experience of participation and had positive views. Many had altruistic reasons for taking part. Multiple-choice questions had high completion rates and free-text fields were less completed. More details on participant research priorities may be gained by offering options to select from. Future investigation of participant experience should also consider those lost to follow-up, participants who choose to withdraw, and potential participants who did not enrol. References: [1] INVOLVE. Approaches to Public Involvement: NIHR; [http://www.invo.org.uk/posttyperesource/approaches-to-public-involvement/] [2] Planner C, Bower P. Trials need participants but not their feedback? A scoping review of measures of participant experience of taking part in trials. School for Primary Care Research - 2017 Showcase Blavatnik School of Government; Oxford: NIHR; 2017 [3] Sergeant JC, Hyrich KL, Anderson J, et al. OP0013 Prediction of Non-Response To Methotrexate Therapy in The Rheumatoid Arthritis Medication Study (RAMS). Annals of the Rheumatic Diseases2016. p. 57-8 Disclosure of Interests: None declared